Community paediatricians' experience of joint working with child and adolescent mental health services: findings from a British national survey. Issue 1 (19th April 2022) - Ani, Cornelius; Ayyash, Hani F; Ogundele, Michael Oladipo
Abstract : Objectives: Children and young people (CYP) presenting to paediatric or child and adolescent mental health services (CAMHS) often have needs spanning medical and psychiatric diagnoses. However, joint working between paediatrics and CAMHS remains limited. We surveyed community paediatricians in the UK to inform better strategies to improve joint working with CAMHS. Methods: We conducted an online survey of community paediatricians through the British Association for Community Child Health (BACCH) on how much joint working they experienced with CAMHS, any hindrances to more collaborative working, and the impact on service users and service provision. This paper is based on thematic analysis of 327 free-text comments by paediatricians. Results: A total of 245 community paediatricians responded to the survey (22% of BACCH members). However, some responses were made on behalf of teams rather than for individual paediatricians. The following were the key themes identified: a strong support for joint working between community paediatrics and CAMHS; an acknowledgement that current levels of joint working were limited; the main barriers to joint working were splintered commissioning and service structures (eg, where integrated care systems fund different providers to meet overlapping children's health needs); and the most commonly reported negative impact of non-joint working was severely limited access to CAMHS for CYP judged by paediatricians to require mental health support, particularly those with autism spectrum disorder. Conclusion: There is very limited joint working between community paediatrics and CAMHS in the UK, which is associated with many adverse impacts on service users and providers. A prointegration strategy that includes joint commissioning of adequately funded paediatric and CAMHS services that are colocated and within the same health management organisations is crucial to improving joint working between paediatrics and CAMHS.